DCAMKL1 is associated with the malignant status and poor outcome in bladder cancer - Shiqing Zhang; Guoqing Zhang; Hongbo Guo (Tumor Biology)
DCAMKL1 (doublecortin and CaM kinase-like 1) has been found to be overexpressed and function as an oncogene in several types of cancer, but there are limited reports on the role of DCAMKL1 in bladder cancer. The messenger RNA and protein expression of DCAMKL1 in bladder cancer tissues and cell lines was measured by quantitative reverse transcription polymerase chain reaction, western blotting, or immunohistochemistry. The correlation between DCAMKL1 protein expression and clinicopathological characteristics was analyzed. Univariate and multivariate Cox regression models were adopted to evaluate prognostic significance of DCAMKL1 in bladder cancer patients. In our results, DCAMKL1 messenger RNA and protein were overexpressed in bladder cancer tissues compared with adjacent normal tissues. DCAMKL1 protein overexpression was positively associated with clinical stage, muscularis invasion, lymph node metastasis, and distant metastasis. The univariate and multivariate analyses suggested DCAMKL1 protein overexpression was an unfavorable prognostic factor in bladder cancer patients. In conclusion, DCAMKL1 is an independent poor prognostic factor for bladder cancer patients.